2013
DOI: 10.1021/jp4089029
|View full text |Cite
|
Sign up to set email alerts
|

Visible–NIR Light Absorption of Titania Thermochemically Fabricated from Titanium and its Alloys; UV- and Visible-Light-Induced Photochromism of Yellow Titania

Abstract: This article reports the optical properties of visible−NIR light absorbing titania powders fabricated by thermochemical oxidation in air of technically pure titanium (99T) and of three titanium alloys ) that contained aluminum as the major impurity (from 0.21 to 6.5 at. %) and other metals indicated in the notations. The resulting titania specimens were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and diffuse reflectance spectroscopy. The titania samples obtained from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…385 nm when exposed to UV/MW and UV/CH irradiation. In accord with earlier studies by Kuznetsov and Serpone, [31][32][33][34] the broad absorption from 370 nm to 700 nm in Fig. 4b is likely the result of two overlapping absorption bands positioned at around 430 nm (B2.90 eV; band AB1) and at ca.…”
Section: Characterization Of St01 Systems -Diffuse Reflectance Spectr...supporting
confidence: 92%
“…385 nm when exposed to UV/MW and UV/CH irradiation. In accord with earlier studies by Kuznetsov and Serpone, [31][32][33][34] the broad absorption from 370 nm to 700 nm in Fig. 4b is likely the result of two overlapping absorption bands positioned at around 430 nm (B2.90 eV; band AB1) and at ca.…”
Section: Characterization Of St01 Systems -Diffuse Reflectance Spectr...supporting
confidence: 92%
“…It will be emphasized that the bismuthates Sr 2 Bi 2 O 5 and Sr 3 Bi 2 O 6 that exhibited relatively wide bandgaps ( Table 3) and were initially somewhat weakly-colored are shown to be photosensitive, while the heavily colored Sr 6 Bi 2 O 11 system ( Figure S1) with the smallest bandgap energy shows no photocoloration. The same peculiarities were displayed by the lightly (yellow) and heavily multi-doped TiO 2 (red and brown) ceramics as reported elsewhere [43].…”
Section: Photodegradaiton Of Phenol In the Presence Of Radical Scavensupporting
confidence: 83%
“…This color change observed subsequent to irradiation was reported in our earlier study and was illustrated in actual photographs shown in Figure 1. 7 Monitoring the kinetics of the absorption changes at each stage of the photochromic transformation provides a novel insight into the charge carrier dynamics. The following three points will be basic for consideration of the experimental data: (1) attribution of photoinduced absorption bands to a set of electronic Ti 3+ centers, 6,7 (2) photoformation of electron−hole pairs under irradiation at 3.05 eV, and (3) total disappearance of all electronic Ti 3+ centers after heating the sample up to 550 K, i.e., total reversibility of the absorption change.…”
Section: Resultsmentioning
confidence: 99%
“…7 Additional long-wavelength illumination causes a decrease of the blue-light-induced absorption spectrum (photobleaching), while such illumination is followed by a significant change in the shape of the UV-induced spectrum. The results obtained were clear experimental indications that the absorption spectra of yellow titania induced by irradiation in the UV or visible regions consist of at least three distinct absorption bands.…”
Section: Resultsmentioning
confidence: 99%